Terminološko načrtovanje in upravljanje terminologije - Gorjanc, Vojko (Slavistična revija, 2010)
The article presents the basic principles of terminology planning, which is understood as management of conceptual innovation both on supra-national and national levels. The framework of terminology planning includes a series of actions that are part of a broader battery of language-planning activities as well as education, translation, and development of science and technology. Theauthor assesses the actions related to terminology planning in Slovenia andputs forward a proposal how to achieve a more coherent terminology planning.
Keywords: Slovene; slovenščina; terminologija; terminology; zbirke podatkov